Automation System and Monitoring in the Hydroponic Cultivation Process Integrated with Internet Network - Abdullah, Abdullah; Kaban, Roberto (Sinkron : jurnal dan penelitian teknik informatika, 2019)
The monitoring system in nutrient solution is something that must be considered in the process of hydroponic cultivation, because it is from this nutrient solution that ensures the result and quality of the hydroponic plant itself. Important variables such as acidity, temperature and concentration of nutrient solution are the values that determine whether or not the nutrient solution will be given to the hydroponic plant. Important variables in improper nutrient solutions will make the hydroponic cultivation process for crop failure. This research uses a PH sensor that serves to detect the acidity level of the nutrient solution and the DHT11 temperature sensor which functions to read the condition of the nutrient solution temperature and the TDS sensor detects the concentration of the nutrient solution. The microcontroller used is the type of Atmega328 which is used as a processing of all inputs and outputs. This monitoring system is connected to the internet so that all sensor reading values can be viewed through an Android phone and can be accessed via the Web, so that the monitoring process can be done remotely. From the test results obtained prove that this system has been successfully integrated and is able to work well according to the desired target, which can monitor the acidity and temperature conditions in hydroponic plants that can be accessed directly through mobile phones and has been integrated with the internet network. Keywords— automation; monitoring; cultivation; hydroponics; internet